Carbon Commodity Linkages in Emerging and Mature Markets: Comparative Evidence from Indonesia and the EU ETS - Firdaus, Naufal Arif Nur; Husnaqilati, Atina (International Journal of Energy Economics and Policy, 2026)
This study investigates the relationship between carbon prices and major food, energy, and mineral commodities in Indonesia and Europe using a multi method framework that includes correlation analysis, hierarchical clustering, random matrix theory (RMT), rolling window eigenvalue diagnostics, and vector autoregression (VAR). The Indonesian dataset (2024–2025) reflects the early stage of the IDX Carbon market, while the European dataset (2015–2025) represents the mature structure of the EU Emissions Trading System. The combination of RMT filtering and VAR modelling allows for the identification of systemic comovement and dynamic transmission channels. The results show a clear contrast between the two markets. In Indonesia, correlation measures, clustering patterns, and RMT indicators suggest that commodity price movements are mostly noise driven, with no stable link between carbon prices and food, energy, or mineral commodities. In Europe, the eigenvalue spectrum, the systemic risk index, and rolling RMT patterns reveal strong and time varying comovement across energy and metal commodities, with VAR results identifying natural gas as the main driver of carbon price dynamics. Overall, the findings highlight how market maturity and energy system structure shape carbon commodity interactions and offer guidance for carbon market design in emerging economies.